Enterprise location choice and regional sustainable development based on the theory of stable matching - Shi, Lifan; Tang, Decai; Kong, Haojia; Boamah, Valentina (Frontiers in Environmental Science, 2022)
As an important path of industrial structure adjustment and upgrading, industrial transfer is of great significance to narrow the regional economic development gap in China and promoting the sustainable development of regional economies. The choice of location of enterprises is not only the leading reason for industrial transfer, but is also crucial for the development of enterprises. From the perspective of bilateral matching, this paper studies the selection of locations by enterprises and how the government attracts investment. The paper also studies the mechanism by which the stable matching between enterprises and the government's inducements to invest are realized. The results show that, based on the stable matching mechanism, a bilateral matching scheme between enterprises and the government can give full play to the decisive role of the markets in resource allocation, maintain long-term stable investment and cooperation between the two sides and help China's industries transfer and upgrade their quality in an orderly fashion.